2008
DOI: 10.1673/031.008.4301
|View full text |Cite
|
Sign up to set email alerts
|

Repellent Properties of δ-Octalactone Against the Tsetse Fly,Glossina morsitans Morsitans

Abstract: δ-octalactone, produced by several Bovidae, has been suggested as a potential repellant of tsetse fly attack. Racemic δ-octalactone was synthesized via an abbreviated route. The product was assayed against 3-day old starved teneral female tsetse flies, Glossina morsitans morsitans Wiedemann (Diptera: Glossinidae), in a choice wind tunnel and found to be a potent tsetse repellent at doses ≥0.05 mg in 200 µl of paraffin oil (0.05 >p >0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…We therefore expanded our test odorant set to include 16 chemically diverse odorants not known to act as pheromones. These odorants include human and animal odorants and compounds previously shown either to attract (1-octen-3-ol and acetone) or repel (δ-nonalactone) G. morsitans (16). All odorants were tested at 10 −2 dilutions in paraffin oil (1% vol/vol), following a precedent set in other studies (10,17), except for methyl laurate, which was used neat.…”
Section: Significancementioning
confidence: 99%
“…We therefore expanded our test odorant set to include 16 chemically diverse odorants not known to act as pheromones. These odorants include human and animal odorants and compounds previously shown either to attract (1-octen-3-ol and acetone) or repel (δ-nonalactone) G. morsitans (16). All odorants were tested at 10 −2 dilutions in paraffin oil (1% vol/vol), following a precedent set in other studies (10,17), except for methyl laurate, which was used neat.…”
Section: Significancementioning
confidence: 99%
“…They suggested that these differences were due to allomones unique to waterbuck. Further investigations showed that the chemical profiles of waterbuck and buffalo differ (Gikonyo et al 2002), that tsetse show electrophysiological responses to these chemicals (Gikonyo et al 2003) and that some of these chemicals elicit upwind flight in olfactometers (Gikonyo et al 2003, Mwangi et al 2008. Curiously, the bioassays of putative allomones did…”
Section: The Role Of Olfaction In Host Selectionmentioning
confidence: 99%
“…Similarly, animal hosts of disease vectors also produce volatiles that protect them from attacks and threats of their enemies. For instance, 3-cresol, guaiacol, geranylacetone, pentanoic acid and δ-octalactone, have been reported to be tsetse fly repellents that are produced by the waterbuck (a non-preferred host) and protect it from attack by the tsetse flies [48,[78][79][80]. Waterbuck allomones have been shown to have the potential of protecting oxen from tsetse flies [80].…”
Section: Plos Onementioning
confidence: 99%